INNOVATIVE APPROACHES IN MODERN PHYSICS RESEARCH: THE IMPORTANCE OF THEORETICAL MODELING AND COMPUTATIONAL METHODS (Universal International Scientific Journal, 2026)
This article reviews contemporary research in modern physics. It covers quantummechanics, relativity theory, cosmology, plasma physics, semiconductor and novel materials physics.The paper also discusses modern theoretical physics methods and computational approaches, includingmathematical modeling, computer simulations, and artificial intelligence applications for analyzingcomplex systems. Examples of current research, such as quantum technologies, tokamak plasmaexperiments, perovskite materials, and Large Hadron Collider studies, are highlighted. The articleprovides a comprehensive overview of both theoretical and applied advances in physics, illustratingfuture prospects for scientific and technological developments.
Keywords: Modern physics; quantum mechanics; theory of relativity